Upaya Pemberdayaan dan Peningkatan Keterampilan Perawatan Jenazah Bagi Ibu-Ibu PKK Se Kecamatan Jombang Kabupaten Jember - Nurhidayati, Titin; Rofiq, M. Nafiur; Hori, Muhammad; Iftitah, Dhurroh (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2023)
So far, caring for corpses is still considered the duty of a village priest or kiyai, even though in Islam caring for corpses is fardlu kifayah, which means that if in one village there is already one person who cares for the corpse, then the other obligations fall, but if there is none who cares for the corpse, all people in one village are sinful. Caring for the corpse is the main obligation for Muslims, namely washing, shrouding, praying, and burying according to Islamic law. Particularly for the treatment of women's corpses, there are very limited numbers of people who can treat corpses. So that when a female member dies at almost the same time, she will experience problems and have to wait a long time for officers to treat the bodies. This service aims to provide understanding and skills to the community, especially women reciting lectures regarding the importance of caring for corpses. The dedication method is carried out for one full day by providing fiqh material related to the chapter of the corpse as well as the practice of caring for the corpse. The results of the dedication show that the mothers of the recitation understand the importance of caring for corpses, and are skilled at caring for corpses.